2022
DOI: 10.2337/dc22-0693
|View full text |Cite
|
Sign up to set email alerts
|

Cambridge Hybrid Closed-Loop System in Very Young Children With Type 1 Diabetes Reduces Caregivers’ Fear of Hypoglycemia and Improves Their Well-being

Abstract: OBJECTIVE To evaluate the impact of CamAPS FX hybrid closed-loop (HCL) automated insulin delivery in very young children with type 1 diabetes (T1D) on caregivers’ well-being, fear of hypoglycemia, and sleepiness. RESEARCH DESIGN AND METHODS We conducted a multinational, open-label, randomized crossover study. Children (age 1–7 years) with T1D received treatment for two 4-month periods in random order, comparing HCL with senso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A total of 23 studies were identified in the literature search as having psychosocial endpoints (Table 8 in the Supplementary Information) [23,29,38,41,44,66,67,76,83,[88][89][90][91][92][93][94][95][96][97][98][99][100][101]. These were analysed separately to the 59 papers included in the systematic review, although eight of the 23 studies were also featured in the systematic review with a focus on their glycaemic endpoints.…”
Section: Psychosocial Outcomesmentioning
confidence: 99%
“…A total of 23 studies were identified in the literature search as having psychosocial endpoints (Table 8 in the Supplementary Information) [23,29,38,41,44,66,67,76,83,[88][89][90][91][92][93][94][95][96][97][98][99][100][101]. These were analysed separately to the 59 papers included in the systematic review, although eight of the 23 studies were also featured in the systematic review with a focus on their glycaemic endpoints.…”
Section: Psychosocial Outcomesmentioning
confidence: 99%
“…1 Previous studies have shown that parental sleep and well-being improved while using AID systems in young children. 31,32 We hypothesize that better parental sleep quality could be one explanation for the decreased treatment-related stress observed in parents of children in our study.…”
Section: Discussionmentioning
confidence: 76%
“… 41 HCL with AID can reduce parental burden for managing diabetes‐related care and reduce perceptions of parenting stress. 42 , 43 Making certified systems with this technology available for children younger than 7 years, tailoring the algorithms to the age‐specific needs of this patient group, and further developing clinical and research experience using this treatment modality in preschool children will be important. Age‐specific challenges to address in automated systems include the small insulin doses needed, often well below 10 U per day, 44 the large differences in physiological insulin needs during different parts of the day, significant day‐to‐day variation in insulin needs, and safety concerns to avoid accidental insulin dosing.…”
Section: Practical Aspects On Use Of Insulin Pumps With and Without C...mentioning
confidence: 99%